2008
DOI: 10.1016/j.pain.2008.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated sodium channel expression in rat and human epidermal keratinocytes: Evidence for a role in pain

Abstract: Keratinocytes are implicated in sensory transduction and can influence nociception, but whether these contribute to chronic pain is not known. In neurons, voltage-gated sodium channels (Na(v)) are involved in neuropathic pain and are activated by depolarization. Since keratinocytes can also show changes in membrane potential, we used RT-PCR, in situ hybridization, and immunohistochemistry to investigate the expression of sodium channels in these cells. Na(v)1.1, Na(v)1.6, and Na(v)1.8 were localized within ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
178
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(192 citation statements)
references
References 56 publications
11
178
1
2
Order By: Relevance
“…The only drugs known to interact with Nav1.2 are the anticonvulsants. Nav1.2 is expressed on keratinocytes and appears to be associated with pain [49]. Carbamazepine and phenytoin bind the same site on Nav1.2.…”
Section: Results: Disproportionate Molecular Targets Identified By Damentioning
confidence: 99%
“…The only drugs known to interact with Nav1.2 are the anticonvulsants. Nav1.2 is expressed on keratinocytes and appears to be associated with pain [49]. Carbamazepine and phenytoin bind the same site on Nav1.2.…”
Section: Results: Disproportionate Molecular Targets Identified By Damentioning
confidence: 99%
“…This might be important in CRPS. For instance, Zhao et al (Zhao et al, 2008) reported that sodium channel expression was increased in the keratinocyte layer of patients with CRPS and post herpetic neuralgia, and the beta-isoform of the inflammatory neuropeptide CGRP was found to be increased in keratinocytes both in CRPS patients and in animal models of pain (Hou et al, 2011).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Sadly enough only fragmentary insight exists in the role and the peripheral expression of sodium channels in pain-transducing free nerve ending in the skin and on the keratinocytes [28]. The sodium channels, Nav1.1, Nav1.6 and Nav1.8 are abundantly present at epidermal keratinocytes [29]. These sodium channel have differential patterns of distribution within the epidermis.…”
Section: Voltage-gated Sodium Channels: a Key Target For Phenytoinmentioning
confidence: 99%
“…Labeled axons within the dermis were detected for Nav1.2, Nav1.7, Nav1.8 and Nav1.9, but its immunolabeling was much less intense compared to the keratinocytes. It was suggested that these channels could possibly contribute to pain [29]. Pathological increases have been documented in keratinocyte sodium channel expression found in skin biopsies of patients suffering from neuropathic pain [29].…”
Section: Voltage-gated Sodium Channels: a Key Target For Phenytoinmentioning
confidence: 99%